2020
DOI: 10.1016/j.gaitpost.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic changes in patients with severe knee osteoarthritis are a result of reduced walking speed rather than disease severity

Abstract: Foundation and Deutsche Arthrose-Hilfe e.V. The funding sources had no involvement in any aspect of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 33 publications
1
25
1
1
Order By: Relevance
“…On the downside, an important issue of gait assessment with IMUs is that it typically results in a large number of outcome parameters, with numerous correlated parameters. For example, many gait parameters share covariance with gait speed [11][12][13][14][15]. Hence, for clinical implementation, it is important to identify gait parameters from independent gait domains that best describe the gait adaptations in individuals with knee and hip OA compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…On the downside, an important issue of gait assessment with IMUs is that it typically results in a large number of outcome parameters, with numerous correlated parameters. For example, many gait parameters share covariance with gait speed [11][12][13][14][15]. Hence, for clinical implementation, it is important to identify gait parameters from independent gait domains that best describe the gait adaptations in individuals with knee and hip OA compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…While most studies on OA using inertial sensor systems have focused on knee OA, a few studies performing measurements with inertial sensor systems in patients with hip OA have reported spatiotemporal parameters [6,9,10,17,18], but none of these captured joint kinematics. Among inertial sensor systems, the RehaGait® system has been shown to provide reliable data that are comparable to an instrumented treadmill and camera-based system for measuring spatiotemporal parameters and lower limb kinematics in younger and older healthy subjects as well as in patients with knee OA and lumbar spinal stenosis [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Although the treatment focused on the knee, the hip ROM increase during gait was the most noteworthy difference observed. We can conclude that the increase in ROM is effectively related to the treatment, as the speed was relatively constant and joint kinematics are speeddependent during gait [32,33]. Previous studies have also shown that changes in gait mechanics in the knee joint affect the ROM of the ankle and hip joints [34,35], possibly explained by the fact that these three joints operate as a kinetic/kinematic chain during gait [34,36].…”
Section: Discussionmentioning
confidence: 80%